Evaluation of the Positive Impact of Tonsillectomy on Children Health Using Glasgow Benefit Inventory - Duraid H. Abid Alkadem; Ali Lafta Salman; Qays Jaafar Khalaf (ACTA MEDICA IRANICA, 2026)
The aim of this survey was to determine the level of health improvement reported by parents of children with a history of chronic tonsillitis who had undergone tonsillectomy in Baqubah City, Iraq. This retrospective cross-sectional study involved a sample of 100 pediatric patients aged 3 to 15 years with previous chronic tonsillitis who underwent tonsillectomy at Baqubah Teaching Hospital. Health improvement was assessed using a self-administered questionnaire known as the Glasgow Benefit Inventory (GBI). This standardized measure consists of 18 retrospective items, each rated on a 5-point Likert scale, and is designed to assess the degree of improvement attributable to surgical intervention. The scale provides a total score and three subscale scores: General Health, Social Support, and Physical Health. Scores are standardized on a scale from -100 to 100, where any positive score indicates improvement in the physical and emotional well-being of patients who have undergone tonsillectomy, whereas negative scores suggest deterioration. Analysis of the findings showed significant differences among the subscale scores, with the Social Support subscale having the lowest score, followed by the General Health subscale, while the Physical Health subscale had the lowest final rank. After tonsillectomy, improvements were observed in the overall GBI score as well as in the General Health, Social Support, and Physical Health subscales. These findings indicate that tonsillectomy has clinical benefits and may help address some claims made against the procedure. This study supports the appropriate use of healthcare budgets and highlights the importance of tonsillectomy in the management of chronic tonsillitis, particularly for otolaryngologists.